RESEPSI MASYARAKAT MANDAR TERHADAP JIN : (Studi Living Quran di Kabupaten Polewali Mandar) - Sulkifli, Sulkifli (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
This research aims to find out the sense of Mandar society toward jin in the Quran context. Field research is held in the Polewali sub-district, Polewali Mandar regency. This research is qualitative research that applies the social-theologist approach. Three methods processed the data in this research. Those methods are observation, interview, and documentation. The result of this research reveals that (1) Mandar Society confesses jin as a spirit created by God that is different from a human being, but both are the same in an obligation, (2) Mandar society confesses a presence of jin influence in human life, such jin can offer benefit to a human being who has a special relationship with it. On the contrary, jin frequently provides a piece of negative information. (3) the perception of Mandar society toward jin agrees with the principle Quran, that is jin is a creature provided to worship Allah such as human crated as well. Because of the purpose of their creation, both have to be responsible hereafter. Farther, Mandar society admits that jin can marry one other, but not for humans. Those indicate that jin in the perception of Mandar society is based on the Quran.